Dampak Trauma Akut pada Mahasiswa Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sumatra Utara yang Mengalami Kecelakaan Lalu Lintas: Studi Kualitatif Deskriptif - Ainul Mardiyah; Amanda Nurul Balqhis; Putri Handayani Rizki; Tri Suci Nur’aini (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Traffic accidents are traumatic events that cause not only physical injuries but also significant psychological impacts, especially among university students. This study aims to describe the forms of acute trauma experienced by students of the Faculty of Da’wah and Communication at the State Islamic University of North Sumatra after experiencing traffic accidents, as well as to examine the impact of acute trauma on students’ psychological, academic, and social conditions. This research uses a descriptive qualitative approach with data collected through in-depth interviews with two students who had experienced traffic accidents. The findings indicate that the acute trauma experienced by students is more dominant in psychological aspects than physical injuries. The symptoms include excessive fear and anxiety, sleep disturbances, recurring traumatic memories, difficulty concentrating, and heightened vigilance when being on the road. Acute trauma affects academic life through decreased concentration and class attendance for some participants, and social life through temporary social withdrawal or, conversely, increased support from family and friends. In coping with trauma, students employ adaptive coping strategies such as social support, spiritual approaches, engaging in positive activities, and gradual emotional regulation. This study highlights the importance of paying attention to students’ mental health after traffic accidents and the need for trauma counseling and support services within the university environment.